Fluktuasi Perdagangan Komoditi Kopi Indonesia-Jerman 2019-2021 - Irsyad Maulana Hidayat (Dinasti Review Publisher, 2024)
This research examines fluctuations in coffee trade between Indonesia and Germany during the 2019-2021 period. Through a qualitative research approach with collection methods from interviews and document studies. The results show that Germany is an important market for Indonesian coffee commodities, and this weakening is influenced by changes in international trade dynamics, competition with other exporting countries, and the impact of the COVID-19 pandemic. The volume of Indonesian coffee exports decreased in 2020 due to the pandemic, but began to recover in 2021. Factors such as import tariffs, environmentally friendly policy regulations in Germany, and coffee quality are the main determinants in the dynamics of coffee trade between the two countries. It is hoped that this research will provide insight to strengthen Indonesia's economic diplomacy and coffee trade strategy with Germany in the future.